2019
DOI: 10.3390/cancers11050623
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Profiling of the Steroidogenic Acute Regulatory Protein in Breast Cancer: In Silico Assessments and a Mechanistic Perspective

Abstract: Cancer is a multifactorial condition with aberrant growth of cells. A substantial number of cancers, breast in particular, are hormone sensitive and evolve due to malfunction in the steroidogenic machinery. Breast cancer, one of the most prevalent form of cancers in women, is primarily stimulated by estrogens. Steroid hormones are made from cholesterol, and regulation of steroid/estrogen biosynthesis is essentially influenced by the steroidogenic acute regulatory (StAR) protein. Although the impact of StAR in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 71 publications
3
23
0
Order By: Relevance
“…BCs are frequently classified based on immunohistochemical (IHC) markers for ER (specifically ERα, but not ERβ), PR, and HER2 into the following subtypes: luminal A, luminal B, HER2, normal-like, and TNBC (in which 15–20% are basal-like) ( Figure 1 ). While luminal A tumors are ER positive (ER+) and/or PR+, and do not express HER2 (HER2−), luminal B subtypes essentially express ER+/PR+ and HER+ [ 2 , 24 , 30 ]. Notably, luminal categories are hormone sensitive and account for over three quarters of all BCs.…”
Section: Overview Of Bc Subtypesmentioning
confidence: 99%
See 1 more Smart Citation
“…BCs are frequently classified based on immunohistochemical (IHC) markers for ER (specifically ERα, but not ERβ), PR, and HER2 into the following subtypes: luminal A, luminal B, HER2, normal-like, and TNBC (in which 15–20% are basal-like) ( Figure 1 ). While luminal A tumors are ER positive (ER+) and/or PR+, and do not express HER2 (HER2−), luminal B subtypes essentially express ER+/PR+ and HER+ [ 2 , 24 , 30 ]. Notably, luminal categories are hormone sensitive and account for over three quarters of all BCs.…”
Section: Overview Of Bc Subtypesmentioning
confidence: 99%
“…While StAR plays an indispensable role in the regulation of steroid biosynthesis, its involvement in BCs remains poorly understood. Conspicuously, we reported that StAR is overexpressed in hormone-responsive BC cells (in comparison with little to none in non-cancerous mammary epithelial cells), in which amplification of the StAR gene is correlated with poor survival of patients afflicted with this deadly disease [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Steroid hormones are largely synthesized in steroidogenic cells of the adrenal, ovary, testis, placenta, and brain; however, they are also produced in a number of extra-adrenal and -gonadal tissues. Glucocorticoids play critical roles in a wide variety of physiological processes, including regulation of various developmental and homeostatic pathways and display several immune functions 3 , 8 . Their release and production are regulated primarily by ACTH (adrenocorticotropic hormone) and indirectly by CRH (corticotropin releasing hormone) 1 .…”
Section: Introduction: Glucocorticoids Autoimmune and Inflammatory mentioning
confidence: 99%
“…Cancer is a multifactorial condition with aberrant growth of cells. Alterations in gene expression result in uncontrolled growth of cells involving tumor progression [ 121 , 122 ]. Human genome is mostly transcribed but not translated, and gene amplification, involving oncogene activation, is a key event in the growth and development of cancers.…”
Section: Aging Underlying Medical Conditions and Their Correlation To...mentioning
confidence: 99%